Adolescents and young adults with type 1 diabetes display a high prevalence of endothelial dysfunction. (February 2015) - Scaramuzza, A E; Redaelli, F; Giani, E; Macedoni, M; Giudici, V; Gazzarri, A; Bosetti, A; De Angelis, L; Zuccotti, G V
Abstract Aim Little is known about endothelial function in adolescents with type 1 diabetes, and we evaluated endothelial dysfunction, using reactive hyperaemia peripheral arterial tonometry (RH‐PAT). Methods This prospective, observational, 1‐year study focused on 73 adolescents with type 1 diabetes, using multiple daily injections or continuous subcutaneous insulin infusion. The subjects were assessed using RH‐PAT, body mass index, blood pressure, fasting lipid profile, glycated haemoglobin, insulin requirements and hours of physical exercise per week. Results Endothelial dysfunction was observed in 56 patients (76.7%), with lower mean RH‐PAT scores (1.26 ± 0.22 versus 2.24 ± 0.48, p < 0.0001) and higher glycated haemoglobin values at baseline (8.27 ± 1.24% versus 7.37 ± 0.54%, p = 0.006) and as a mean of the whole period since diagnosis (8.25 ± 1.22% versus 7.72 ± 0.82%, p = 0.034). A higher percentage of patients with endothelial dysfunction showed abnormal cardiac autonomic tests (p = 0.02) and were more sedentary, exercising <4 hours a week, than patients with normal endothelial function. After follow‐up in 64/73 patients, we observed endothelial dysfunction in 81.8% of patients, despite a modest improvement in glycated haemoglobin. Conclusion Adolescents with type 1 diabetes displayed evidence of endothelial dysfunction. Good metabolic control (glycated haemoglobin ≤7.5%, 58 mmol/mol) and regular physical activity of at least 4 h a week might be protective.